The dragon-II simulations - II. Formation mechanisms, mass, and spin of intermediate-mass black holes in star clusters with up to 1 million stars - Arca Sedda, Manuel; Kamlah, Albrecht; Spurzem, Rainer; Rizzuto, Francesco Paolo; Naab, Thorsten; Giersz, Mirek; Berczik, Peter (Monthly notices of the Royal Astronomical Society, 2023)
The processes that govern the formation of intermediate-mass black holes (IMBHs) in dense stellar clusters are still unclear. Here, we discuss the role of stellar mergers, star-BH interactions, and accretion, as well as BH binary (BBH) mergers in seeding and growing IMBHs in the Dragon-II simulation database, a suite of 19 direct N-body models representing dense clusters with up to 106 stars. Dragon-II IMBHs have typical masses of mIMBH = (100-380) M⊙ and relatively large spins χIMBH > 0.6. We find a link between the IMBH formation mechanism and the cluster structure. In clusters denser than 3 × 105 M⊙ pc−3, the collapse of massive star collision products represents the dominant IMBH formation process, leading to the formation of heavy IMBHs (mIMBH > 200 M⊙), possibly slowly rotating, that form over times <5 Myr and grow further via stellar accretion and mergers in just <30 Myr. BBH mergers are the dominant IMBH formation channel in less dense clusters, for which we find that the looser the cluster, the longer the formation time (10-300 Myr) and the larger the IMBH mass, although remaining within 200 M⊙. Strong dynamical scatterings and relativistic recoil efficiently eject all IMBHs in Dragon-II clusters, suggesting that IMBHs in this type of cluster are unlikely to grow beyond a few 102 M⊙.
Vorab online veröffentlicht: 25. September 2023
Gesehen am 26.01.2024